2017
DOI: 10.1364/boe.8.001405
|View full text |Cite
|
Sign up to set email alerts
|

Hyperopic Q-optimized algorithms: a theoretical study on factors influencing optical quality

Abstract: Abstract:In this work, we analyze the way in which pupil size, optical zone, and initial hyperopic level influence optical quality for hyperopic Q-optimized corneal refractive surgery. Different Q-optimized algorithms and the Munnerlyn formula were tested to analyze the optical quality of the final retinal image for initial hyperopic errors from 1D to 5D. Three optical zones (5.5, 6, and 6.5 mm) and two pupil diameters (5 and 7 mm) were considered. To evaluate optical quality, we computed the modulation transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…In LASIK, monovision is a method of presbyopic correction, in which one eye is corrected for distance vision and the other eye for near vision, and this procedure is based on Q factor modulation. In addition, the Q factor was adjusted in both eyes, which induced an increase in the negative Q factor and improved the prolate shape (hyperprolateness) of the cornea 20 , and using Q-optimized algorithms improves visual quality for myopia in terms of the modulation transfer function (MTF) 21 , 22 . Our analysis showed that NaF strip application did not cause a statistically significant change in the measurement of Q value; therefore, we considered that NaF strip intervention would not significantly influence the preoperative planning in LASIK with a custom Q-ablation profile.…”
Section: Discussionmentioning
confidence: 99%
“…In LASIK, monovision is a method of presbyopic correction, in which one eye is corrected for distance vision and the other eye for near vision, and this procedure is based on Q factor modulation. In addition, the Q factor was adjusted in both eyes, which induced an increase in the negative Q factor and improved the prolate shape (hyperprolateness) of the cornea 20 , and using Q-optimized algorithms improves visual quality for myopia in terms of the modulation transfer function (MTF) 21 , 22 . Our analysis showed that NaF strip application did not cause a statistically significant change in the measurement of Q value; therefore, we considered that NaF strip intervention would not significantly influence the preoperative planning in LASIK with a custom Q-ablation profile.…”
Section: Discussionmentioning
confidence: 99%
“…The main focus of this study was the optical performance, but we will consider the effect of the interactive optical-neural performance on visual perception in our following studies. Although designed for Femto-LASIK, this eye modeling method could be utilized in other types of myopic surgeries 4 and corneal surgeries, such as treatments of hyperopia 61 and keratoconus 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Differing from our comprehensive approach, several studies have emphasized the optimization of specific postoperative outcomes to improve visual quality. 23,24 Previous researches have tried to minimize differences between the real ablation and the predicted one using a quadratic term in the formulae. 25 The recent study demonstrated that a surgeon should consider the nonlinear relationships between optical variables using the Q-optimized algorithm.…”
Section: Discussionmentioning
confidence: 99%